Posturografia do Balance Rehabilitation Unit (BRU TM) na vertigem posicional paroxística benigna - Monteiro, Silvia Roberta Gesteira (2012)
Posturography has been used in the evaluation of patients with vestibular disorders. AIM: To evaluate balance control with the Balance Rehabilitation Unit (BRU TM) posturography in patients with Benign Paroxysmal Positional Vertigo. Study design: Prospective case-control. MATERIALS AND METHODS: A cross-sectional controlled study was carried out in 45 patients with BPPV, and a homogeneous control group consisting of 45 healthy individuals. Patients were submitted to a balance function evaluation by means of the Balance Rehabilitation Unit (BRU TM) posturography. RESULTS: The mean values of the ellipse area and the sway velocity in a firm surface and saccadic stimulation (p = 0.060). CONCLUSION: The Balance Rehabilitation Unit (BRU TM) posturography enables to identify postural control abnormalities in patients with BPPV.